Comparison of proton therapy treatment planning for head tumors with a pencil beam algorithm on dual and single energy CT images - Hudobivnik, Nace; Schwarz, Florian; Johnson, Thorsten; Agolli, Linda; Dedes, George; Tessonnier, Thomas; Verhaegen, Frank; Thieke, Christian; Belka, Claus; Sommer, Wieland H.; Parodi, Katia; Landry, Guillaume (Medical physics, 2016)
Purpose: Dual energy CT (DECT) has recently been proposed as an improvement over single energy CT (SECT) for stopping power ratio (SPR) estimation for proton therapy treatment planning (TP), thereby potentially reducing range uncertainties. Published literature investigated phantoms. This study aims at performing proton therapy TP on SECT and DECT head images of the same patients and at evaluating whether the reported improved DECT SPR accuracy translates into clinically relevant range shifts in clinical head treatment scenarios. Methods: Two phantoms were scanned at a last generation dual source DECT scanner at 90 and 150 kVp with Sn filtration. The first phantom (Gammex phantom) was used to calibrate the scanner in terms of SPR while the second served as evaluation (CIRS phantom). DECT images of five head trauma patients were used as surrogate cancer patient images for TP of proton therapy. Pencil beam algorithm based TP was performed on SECT and DECT images and the dose distributions corresponding to the optimized proton plans were calculated using a Monte Carlo (MC) simulation platform using the same patient geometry for both plans obtained from conversion of the 150 kVp images. Range shifts between the MC dose distributions from SECT and DECT plans were assessed using 2D range maps. Results: SPR root mean square errors (RMSEs) for the inserts of the Gammex phantom were 1.9%, 1.8%, and 1.2% for SECT phantom calibration (SECTphantom), SECT stoichiometric calibration (SECTstoichiometric), and DECT calibration, respectively. For the CIRS phantom, these were 3.6%, 1.6%, and 1.0%. When investigating patient anatomy, group median range differences of up to −1.4% were observed for head cases when comparing SECTstoichiometric with DECT. For this calibration the 25th and 75th percentiles varied from −2% to 0% across the five patients. The group median was found to be limited to 0.5% when using SECTphantom and the 25th and 75th percentiles varied from −1% to 2%. Conclusions: Proton therapy TP using a pencil beam algorithm and DECT images was performed for the first time. Given that the DECT accuracy as evaluated by two phantoms was 1.2% and 1.0% RMSE, it is questionable whether the range differences reported here are significant.
Gesehen am 02.06.2020